From the History of the Terminology in Linguistics: Reading Y. Sheveliov (Linguostylistic Studies, 2018)
Yuriy Sheveliov (Sherekh) is a well-known linguist. He is a specialist in the history of language, the history of the Ukrainian literary language, phonology, historical morphology, lexicology, grammar, sociolinguistics, linguistic stylistics. Linguistic poetics is of particular interest for the scholar. Such a wide range of interests did not understate the scientific prudence and profundity of his thoughts in each of the mentioned branches of linguistics. The scholar with his broad erudition has possessed a prominent place in the history of linguistics, both theoretical and practical. The purpose of the research is to analyze the works of Y. Sheveliov related to the study of the Ukrainian literature, texts of poetry and prose; to trace the genesis of the Ukrainian linguistic stylistics as a science since the 30s and 40s of the 20th century and to verify the peculiarities of the methods and techniques of the integrative approach to the analysis of the specific individual-author writing practices, to identify (to specify) the terminological apparatus of the research.The article focuses on the theoretical conceptions of Yu. Sheveliov in the field of linguistic stylistics and linguistic poetics and analyzes his contribution to the development of this branch.  The key theoretical and practical issues related to the development of the methodological tools of the Ukrainian linguistic stylistics since the period of its formation as a separate branch of linguistics (in particular since the 40s of the twentieth century) are highlighted. The author lays emphasis on those style categories on which the research of the language and style of the Ukrainian writers of the late 18th–early 20th century was focused. The study elucidates the advantages of Shevelev’s general philological methodology in the study of literary works and the integrative approach appropriateness to the analysis of the specific texts. Shevelev’s approach involves the synthesis of literary-critical, linguistic and artistic aspects of the analysis.Scrupulous reading of the scientific works by Y. Shevelov gives grounds to argue that, on the one hand, he preserved the foundations of the Ukrainian linguistic stylistics at the beginning of the twentieth century, developed and extended its applicability to the study of a wider range of texts than the official Soviet ideology “allowed”, significantly complete the series of “Linguistic portraits” of outstanding participants in the historical-linguistic process in Ukraine, and, on the other hand, he has significantly deepened content of both the established linguistic-style categories and the integrative principles of the Ukrainian literature.The key findings of the study provide further prospects for the investigation of the scientific works of Y. Sheveliov in the field of philology, in particular the study of his terminology apparatus with a focus on his understanding of certain concepts and categories in the historiography of linguistics.
Keywords: linguistic stylistics; linguistic poetics; linguistic personology; stylistic line; Church Slavonicism; stylization; dialogism